An Evaluation of Environmental and Social Accounting of Diamond Mining Companies in Zimbabwe: a Case of Marange Resources (Pvt) Ltd (Chiadzwa) - Singe, Ability (Midlands State University, 2017)
The study investigated best practice of environmental accounting among companies currently operating in Chiadzwa Mutare specifically Marange Resources (Pvt) Ltd. Precisely, the study assessed the level of independence of tracking of costs impacting on the environment; level of efficiency and appropriateness of environmental costs and disclosure reporting.The study used research instruments such as primary data survey and secondary data elucidation. For this purpose, longitudinal content analyses were carried out. Mode technique is the statistical technique used for the research.Discoveries are that environmental operating expenditures are not charged independently of other expenditures. There is also, absence of costing system for tracking of externality costs. Considering the current limited exposure of many organizations to environmental accounting methodology, this study proffers an insight into new bases and design for environmental accounting. Recommendations among others are that corporate organizations should develop Plans and Operating Guidelines that they may use for their operations.